Adolescent and Young Adult Testicular Germ Cell Tumors: Special Considerations - Amanda F. Saltzman; Nicholas G. Cost (Advances in Urology)
While testicular germ cell tumors (T-GCTs) make up only 0.5% of pediatric malignancies and less than 2% of adult malignancies, they comprise 14% of adolescent malignancies, making it the most common solid tumor in this age group. The transition in incidence at this age is also accompanied by a transition in tumor histology with adolescents having mostly pure embryonal carcinoma and mixed nonseminomatous germ cell tumors. Similar to T-GCTs of all ages, surgical excision with orchiectomy is the standard initial step in treatment. Chemotherapy, retroperitoneal lymph node dissection, and targeted treatment of distant metastases make even widely disseminated disease treatable and curable. For this reason, in many ways, the future focus has expanded beyond survival alone to emphasize quality of life issues such as fertility and hypogonadism. However, adolescents remain the age group least studied or understood as they fall in between the ages included in most study designs. Also, they require the most psychosocial support because of the challenges unique to the adolescent period. In this review, we aim to highlight the known outcome data for T-GCTs in this population and also to discuss the unique aspects of treatment and support for this age group.